Rhetoric of Prophet Abraham and Prophet Joseph Peace Upon Them - Nurbaini Futuhat Wulansari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2023)
Rhetoric of da'wah will determine the success or failure of a